Magnetic anisotropy of transition metal and lanthanide ions in pentagonal bipyramidal geometry. (30th March 2022) - Sutter, Jean-Pascal; Béreau, Virginie; Jubault, Valentin; Bretosh, Kateryna; Pichon, Céline; Duhayon, Carine
Abstract : The magnetic anisotropy associated with a pentagonal bipyramidal coordination sphere is examined on the basis of experimental and theoretical investigations; effects of crystal field, structural distortion, and second coordination sphere are discussed. Abstract : The magnetic anisotropy associated with a pentagonal bipyramidal (PBP) coordination sphere is examined on the basis of experimental and theoretical investigations. The origin and the characteristics of this anisotropy are discussed in relation to the electronic configuration of the metal ions. The effects of crystal field, structural distortion, and a second-coordination sphere on the observed anisotropies for transition meal and lanthanide ions are outlined. For the Ln derivatives, we focus on compounds showing SMM-like behavior ( i.e. slow relaxation of their magnetization) in order to highlight the essential chemical and structural parameters for achieving strong axial anisotropy. The use of PBP complexes to impart controlled magnetic anisotropy in polynuclear species such as SMMs or SCMs is also addressed. This review of the magnetic anisotropies associated with a pentagonal bipyramidal coordination sphere for transition metal and lanthanide ions is intended to highlight some general trends that can guide chemists towards designing a compound with specific properties.